2020
DOI: 10.3389/fnagi.2020.00081
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Retinal Thickness Predicts Age-Related Changes in Cognitive Function

Abstract: Currently, there is a lack of biomarkers to identify individuals in the early stages of Alzheimer's disease (AD). A preponderance of evidence suggests that neurodegenerative processes that affect the brain, may also affect the retina. Using optical coherence tomography (OCT), a non-invasive approach, many have shown thinning of the retina in AD and the developmental precursor to AD, mild cognitive impairment (MCI). However, the relationship between retinal thickness and cognitive function is not entirely clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…It is also consistent with a study that investigated the relationship between the clock‐drawing test and cerebral blood flow in healthy patients, AD patients and MCI patients using single‐photon emission computed tomography, which showed that patients with lower scores on the clock‐drawing tests had a lower blood flow to the bilateral hippocampus 36 . A recently published trial by Mammadova et al 37 . reported RNFL thickness decreases in parallel with cognitive function in certain cognitive domains such as working memory, psychomotor speed and executive function, assessed by performing an extensive neuropsychological evaluation in cognitively healthy individuals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is also consistent with a study that investigated the relationship between the clock‐drawing test and cerebral blood flow in healthy patients, AD patients and MCI patients using single‐photon emission computed tomography, which showed that patients with lower scores on the clock‐drawing tests had a lower blood flow to the bilateral hippocampus 36 . A recently published trial by Mammadova et al 37 . reported RNFL thickness decreases in parallel with cognitive function in certain cognitive domains such as working memory, psychomotor speed and executive function, assessed by performing an extensive neuropsychological evaluation in cognitively healthy individuals.…”
Section: Discussionsupporting
confidence: 89%
“…It is also consistent with a study that investigated the relationship between the clock-drawing test and cerebral blood flow in healthy patients, AD patients and MCI patients using single-photon emission computed tomography, which showed that patients with lower scores on the clock-drawing tests had a lower blood flow to the bilateral hippocampus. 36 A recently published trial by Mammadova et al 37 We propose a hypothesis to explain these findings: the visual associative cortex, located in the inferior temporal lobe and occipital lobe, is particularly vulnerable to neurofibrillary tangles and betaamyloid plaque deposits, which could interrupt neural connections in the visual pathway and provoke a retrograde neuronal degeneration of the optic nerve, thus causing RNFL thinning.…”
Section: Discussionmentioning
confidence: 90%
“…AD was diagnosed using the Diagnostic and Statistical Manual of Mental Disorders(DSM-IV) criteria, National Institute of Neurologic and Communicative Disorders and Stroke-Alzheimer’s Disease and Related Disorders Association 23 criteria or generally through a combination of both approaches. The most common method to diagnose MCI was through the Peterson’s criteria 24 which identifies whether all five criteria are satisfied including, memory complaint corroborated by an informant, objective memory decline, normal general cognitive function, normal functional activities and absent dementia diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, 45.5% of studies using OCT devices to measure RNFL thickness have identified a positive correlation with cognitive impairment, although studies with larger sample sizes (eg, Sánchez et al ,31 930; van de Kreeke et al ,32 298) found no significant correlation. Indeed, researchers have failed to consistently identify a correlation between retinal scanning and cognitive impairment, for example, two recent articles identified an association23 24 with RNFL whereas two articles did not 33 34. This lack of consistency is reflected across all retinal areas and the discrepancies may in part be ascribed to differences in sample size, the severity of cognitive impairment, and the OCT technology used in various devices.…”
Section: Discussionmentioning
confidence: 99%
“…Research found that the reduction in the magnitude of macular RNFL volume significantly correlated with the performance of participants' abilities on a task to efficiently integrate visual and auditory speech information (Santos et al, 2018). A study on a few samples showed that RT correlated with the neuropsychological performance in multiple cognitive domains (e.g., working memory, psychomotor speed, and executive function; Mammadova et al, 2020). However, there are a few studies that have examined the correlation between RT in patients with AD (AD-RT) and various cognitive domains, including memory, attention, language, visuospatial ability, and executive function, as well as neuropsychiatric symptoms, such as anxiety, depression, and agitation.…”
Section: Introductionmentioning
confidence: 99%